Development of Telecommunication System Learning Media with Digital-based ADDIE Method - Saripudin, Saripudin; Bonok, Zainudin; Wiranto, Ifan; Abdussamad, Syahrir; Tansa, Salmawaty; Nasibu, Iskandar Zulkarnain (Electrical Engineering Department Faculty of Engineering State University of Gorontalo, 2025)
High demand and digital penetration in various aspects of human life has directly created a huge industry in technology. This is reflected in the impact of the widespread use of Information and Communication Technology (ICT) which allows for a more efficient way of providing education that makes it easier for educators, students, and students. The purpose of this research is to create a product on the development of learning media in telecommunications systems courses using the digital-based ADDIE method. This research is an RD (Research and Development) development research that uses the ADDIE model, which consists of five stages, namely 1.) Analyze; 2.) Design; 3.) Development; 4.) Implementation; and 5.) Evaluation. The learning media developed is a website that can be used for the Telecommunication System course at the Department of Electrical and Computer Engineering, Faculty of Engineering, Gorontalo State University. The results of this research are in the form of website-based learning media that can be used for the learning process of Telecommunication Systems courses and have been adjusted to the needs based on the needs analysis at the Department of Electrical and Computer Engineering, Faculty of Engineering, Gorontalo State University. Permintaan yang tinggi dan penetrasi digital di berbagai aspek kehidupan manusia secara langsung telah menciptakan industri besar dibidang teknologi. Hal ini tercermin dari dampak meluasnya penggunaan Teknologi Informasi dan Komunikasi (TIK) yang memungkinkan terselenggaranya cara yang lebih efisien dalam memberikan edukasi Pendidikan yang memudahkan bagi para tenaga pendidik, siswa, dan mahasiswa. Tujuan penelitian ini adalah untuk membuat produk pada pengembangan media pembelajaran di mata kuliah sistem telekomunikasi dengan menggunakan metode ADDIE berbasis digital. Penelitian ini merupakan penelitian pengembangan RD (Research and Development) yang menggunakan model ADDIE, yang terdiri dari lima tahap yakni 1.) Analysis; 2.) Design; 3.) Development; 4.) Implementation; end 5.) Evaluation. Media pembelajaran yang dikembangkan merupakan sebuah website yang dapat digunakan untuk mata kuliah Sistem Telekomunikasi pada Jurusan Teknik Elektro dan Komputer Fakultas Teknik Universitas Negeri Gorontalo. Hasil penelitian ini berupa media pembelajaran berbasis website yang dapat digunakan untuk proses pembelajaran mata kuliah Sistem Telekomunikasi dan telah di sesuaikan dengan kebutuhan berdasarkan analisis kebutuhan pada Jurusan Teknik Elektro dan Komputer Fakultas Teknik Universitas Negeri Gorontalo.